Carrier-Envelope Phase Control over Pathway Interference in Strong-Field Dissociation of H+2 - Kling, Nora G.; Betsch, K. J.; Zohrabi, M.; Zeng, S.; Anis, F.; Ablikim, U.; Jochim, Bethany; Wang, Z.; Kübel, M.; Kling, M. F.; Carnes, K. D.; Esry, B. D.; et al. (My University, 2013)
The dissociation of an H+2 molecular-ion beam by linearly polarized, carrier-envelope-phase-tagged 5 fs pulses at 4×1014 W/cm2 with a central wavelength of 730 nm was studied using a coincidence 3D momentum imaging technique. Carrier-envelope-phase-dependent asymmetries in the emission direction of H+ fragments relative to the laser polarization were observed. These asymmetries are caused by interference of odd and even photon number pathways, where net zero-photon and one-photon interference predominantly contributes at H++H kinetic energy releases of 0.2–0.45 eV, and net two-photon and one-photon interference contributes at 1.65–1.9 eV. These measurements of the benchmark H+2 molecule offer the distinct advantage that they can be quantitatively compared with ab initio theory to confirm our understanding of strong-field coherent control via the carrier-envelope phase.